Pengaruh Karakteristik Usaha Dan Wirausaha Terhadap Kinerja UMKM Industri Pengolahan Perikanan Di Provinsi Sulawesi Selatan - Dian Sudiantini; Haikal Azam Masyari; Hanum Najmi Hawa; Khomarudin Jein; Idza Ardhi Wa’afin (Lembaga Pengembangan Kinerja Dosen, 2023)
Research on the influence of business and entrepreneurial characteristics on the general performance of the fisheries processing industry is more specifically reviewed and also researched from an area in Sulawesi, more precisely South Sulawesi Indonesia's large capture fisheries potential can be used as an opportunity to build a fish processing industry, especially in South Sulawesi Province which has a spatial structure policy that supports the fisheries subsector as a superior subsector. Based on the SWOT analysis, strategies that can be applied to encourage the development of the fish processing industry in South Sulawesi Province include strengthening integrated fish processing groups, utilizing and maintaining available catch handling facilities, developing market reach, facilitating administrative access to the establishment of fish processing industries, and increasing the competitiveness of production volumes of fishermen's catches in South Sulawesi Province.South Sulawesi has a specificity in superior products and the quality of human resources, so the policies implemented in the national are not necessarily suitable for South Sulawesi. An appropriate and comprehensive strategy for the development of MSME iin the fisheries processing industry in order to improve their performance in South Sulawesi Province needs to be determined using a way that is in accordance with realistic circumstances and can be applied in reality.